The Effect of Financial Performance on Company Value with Corporate Social Responsibility Disclosure as a Moderating Variable (Study on LQ45 Banking Companies on the Indonesia Stock Exchange) - Dimas Bahar; Geni Mukti; Mego Wibowo (www.amertainstitute.com, 2025)
The research seeks to examine the effect of economic results on organizational value, and to consider how Corporate Social Responsibility (CSR) plays a moderating role in banks within the context of the LQ45 index at the Indonesia Stock Exchange from 2021 to 2023. Financial performance was measured using Return on Assets (ROA), Current Ratio (CR), Debt to Asset Ratio (DAR), while firm value was proxied by Tobin's Q and CSR by the disclosure index (CSRI). The analytical technique employed was multiple linear regression and Moderated Regression Analysis (MRA). This analysis revealed that ROA, CR, and DAR significantly boosted firm value. Additionally, CSR has been shown to reinforce the connection between financial performanceand firm value, particularly through the significant interactions of ROA×CSRI and CR×CSRI. Thus, banking firms that consistently disclose CSR tend to have higher firm value.